2019
DOI: 10.5935/abc.20190027
|View full text |Cite
|
Sign up to set email alerts
|

Stent versus Coronary Artery Bypass Surgery in Multi-Vessel and Left Main Coronary Artery Disease: A Meta-Analysis of Randomized Trials with Subgroups Evaluation

Abstract: Background Comparison between percutaneous coronary intervention (PCI) using stents and Coronary Artery Bypass Grafting (CABG) remains controversial. Objective To conduct a systematic review with meta-analysis of PCI using Stents versus CABG in randomized controlled trials. Methods Electronic databases were searched to identify randomized trials comparing PCI using Stents versus CABG for multi-vessel and unprotected left main coronary artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…However, PCI had a lower incidence of stroke than CABG (0.3% versus 1.5%, P-value 0.001). The two factors that had the most negative effects on PCI findings were diabetes and having a high SYNTAX score (33) .…”
Section: Discussionmentioning
confidence: 99%
“…However, PCI had a lower incidence of stroke than CABG (0.3% versus 1.5%, P-value 0.001). The two factors that had the most negative effects on PCI findings were diabetes and having a high SYNTAX score (33) .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the evidence regarding revascularization of patients with DM and left main disease has been obtained from subgroup analyses of clinical trials, as no study to date has focused only on this population (25). Although being the best available evidence to date, these results should be analyzed with caution, especially because they may not be properly powered for the subgroup with DM (26).…”
Section: Left Main Diseasementioning
confidence: 99%
“…[2][3][4][5][6] Recently, these data were compiled in two meta-analysis where long term follow-up has shown no significant difference in mortality and stroke rate between PCI and CABG. 7,8 In addition, two of these randomized trials with extended long-term followup, up to 10 years, have demonstrated sustained good results after PCI, with death rates similar to CABG, respectively, 14.5% x 13.8% and 27% x 28%. 4,5 In this issue of Arquivos Brasileiros de Cardiologia, Grion et al 9 present their experience with PCI for ULMCA disease in a consecutive series of 107 patients.…”
mentioning
confidence: 99%